2018
DOI: 10.1016/j.dib.2018.08.080
|View full text |Cite
|
Sign up to set email alerts
|

Data on nephroprotective effect of all-trans retinoic acid in early diabetic nephropathy

Abstract: Data showed in this report are related to the research article entitled “All-trans retinoic acid ameliorates inflammatory response mediated by TLR4/NF-кB during the initiation of diabetic nephropathy” by Sierra-Mondragon et al. (2018) [1]. Diabetic nephropathy (DN) has become the main cause of renal failure. Inflammatory molecules such as cytokines, chemokines and growth factors play a key role in DN-induced renal injury Pichler et al. (2016) [2]. Results illustrate the effect of all-trans retinoic acid (ATRA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…The cellular action of ATRA is mediated through RAR-α, β and γ, these receptors directly activate gene transcription [12]. We previously demonstrated that ATRA is a potent nephroprotective agent; its administration exerts antioxidant effects [17] and anti-inflammatory effects during initiation of DN [18,19]. These studies suggested that changes in ATRA signaling via the extracellular/intracellular ATRA level or the expression/activation of RAR-α, closely correlate with the development of diabetes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cellular action of ATRA is mediated through RAR-α, β and γ, these receptors directly activate gene transcription [12]. We previously demonstrated that ATRA is a potent nephroprotective agent; its administration exerts antioxidant effects [17] and anti-inflammatory effects during initiation of DN [18,19]. These studies suggested that changes in ATRA signaling via the extracellular/intracellular ATRA level or the expression/activation of RAR-α, closely correlate with the development of diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…Inflammation plays a critical role in the initiation and progression of renal fibrosis [1,2,3]. We have recently demonstrated that an inflammatory process is induced in initial stages of DN with increased cytokines, chemokines, cell adhesion molecules, and growth factors in glomeruli and proximal tubules [18,19]. However, further understanding of the mechanisms behind renal fibrogenesis is essential to develop therapies to prevent or reverse this process and slow its progression in DN to end-stage renal disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation